LAND LEASE INFORMATION PRESENTATION AT THE TOMB OF GOOD OR SERVICE RATE PUBLIC FUNERAL KARET BIVAK JAKARTA PUSAT - Asep Asep; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2002)
Establishment of Office of the General Cemetery of DKI Jakarta is in the framework of planning and ordering the city, considering the population of Jakarta is increasingly crowded and limited land that could be provided for the public funeral. On the other hand the demands of public services also increased, especially in the field of public funeral service. Through this writing, the author tries to give input and recommendations to the Office Funeral services-making particularly regarding land use permits and renew permits the tomb of the use of cemetery land by using computer-based media.After analyzing and observing the existing activities by coming directly to the location and conduct interviews, the authors found several constraints faced by the Office of Public Cemetery. Among them for making land use permits and renew permits cemetery land use tomb, is still done with rocks stationery. Recording each incoming data still using ledger and to store any data, still archived into thegeneral ledger.Funeral Service proposal writer to permit them to make use of cemetery land, the officers no longer use typewriters, but by using computer-based media are equipped Visual Basic 6.0 application software, officers can directly input the dataand can print directly permit in question, whereas to renew permits the use of cemetery land, the officers did not have to check and see the documents in a large book but an officer can.